Advances on the indigenous special jurisdiction in northern Cauca - Vitonas, Deiby Anderson (2019)
Recognition of indigenous people’s rights appears in the American context since the promulgation of the nineteen’s constitutions, considered to be multicultural, enabling the analysis of the complexity of cultural and juridical diversity taking legal pluralism as the theoretical framework. Such context facilitates the recognition of ethnic diversity and the indigenous people's ways of living embodied in their own system of law and justice administration, allowed in the 1991 Constitution of Colombia. This provides the opportunity for indigenous people to exercise self-governance and apply their own justice according to the people's cosmovision that characterizes, especially, the Nasa community of Northern Cauca, aiming to preserve the cultural identity that defines them. This article will provide an analysis of the Indigenous Special Jurisdiction and its respective advances in the Nasa community of Northern Cauca.